Malnutrition Matters: Impact of Nutritional Status on Early Childhood Development in Nepal. (7th June 2021) - Shrestha, Manisha; Weissman, Amy; Thapa, Basant; Adhikari, Ramesh; Perry, Kelly
Abstract: Objectives: Malnutrition is associated with sub-optimal brain development, which adversely affects cognitive development in children. However, limited information exists in Nepal on the effects of various types of malnutrition on early childhood development (ECD). We assessed the association of stunting, wasting and underweight (three prominent forms of malnutrition) with the four domains of the ECD index (literacy-numeracy, physical, social-emotional and learning development) among children 36 to 59 months of age. Methods: This study used a recently published national household survey from Nepal, the Multiple Indicator Cluster Survey (MICS) 2019 dataset. Unadjusted and adjusted logistic regression was used to identify the association between ECD indicators and stunting, wasting and underweight. The study sample consisted of children aged 3–4 years (n = 2870). Children were considered developmentally on track if they met specific criteria in each of the four ECD domains. Results: Results indicated that 43.9% of stunted, 8.2% wasted and 29.6% underweight children did not sufficiently meet ECD index criteria to be considered developmentally on track. Adjusted odds ratios (OR) indicated that children with literacy-numeracy skills (stunting OR 0.53, p < 0.01, CI 0.42 – 0.67; underweight OR 0.61, p < 0.01, CI 0.47 – 0.79) were adequately nourished (stunting OR 0.47, p < 0.01, CI 0.29 – 0.75; underweight OR 0.55, p < 0.01, CI 0.34 – 0.88), and children with adequate learning development were less likely to be stunted or underweight (stunting OR 0.54, p < 0.01, CI 0.40 – 0.74; underweight OR 0.54, p < 0.01, CI 0.39 – 0.75). However, the study demonstrated no significant association between malnutrition and social-emotional development after adjusting for confounding variables. Likewise, no association between the four ECD domains and child wasting was observed after adjusting for socio-economic confounders. Conclusions: Children's nutrition status impacts ECD outcomes. For better development outcomes among children, ECD components should be integrated into nutrition programming through capacity building activities of mothers, coupling nutrition messaging with ECD and providing books and tools for early learning. Funding Sources: Family Health International (FHI 360).